Two Cases of Small Cell Cancer of the Maxillary Sinus Treated with Cisplatin plus Irinotecan and Radiotherapy - Tsukahara, Kiyoaki (Hindawi Publishing Corporation, 2013)
Background. Small cell carcinoma (SmCC) in the nasal cavity and paranasal sinuses is very rare, and definitive therapies have not yet been established. Methods. Chemoradiotherapy comprised 60 Gy of external radiation, with the administration of irinotecan intravenously at 60 mg/m(2) on days 1, 8, and 15 and cisplatin at 60 mg/m(2) on day 1. Results. Case 1 involved a 66-year-old woman with stage III cancer. Adverse events included decreased white blood cells, anemia, and oral mucositis, all Grade 2. The patient remained free of cancer as of 3 years and 6 months after completing the treatment. Case 2 involved a 60-year-old man with stage IV cancer. He also experienced adverse events of decreased white blood cells, anemia, and oral mucositis, all Grade 2. He died after 11 months due to metastases throughout the body. Conclusions. The results suggest that this regimen may be tolerable as a therapy for this type of carcinoma.